University and academics' societal engagement in Sub-Saharan Africa : benefits, drivers and constraints of knowledges production - Zavale, Nelson Casimiro, 1982-; Schneijderberg, Christian (New York : Routledge, 2024)
"This book provides a comprehensive account of the patterns of university and academics' societal engagement in Sub-Saharan Africa (SSA), considering knowledges production and the resulting outputs, outcomes and benefits that are yielded from such engagement for society. Responding to the call for increased visibility of otherwise marginalised voices in SSA's extant global literature on knowledges production, chapters in the book explore questions around knowledge-based economies, forms of knowledges, and suggest an alternative framework to overcome conventional bias and limits present in prominent concepts, such as National Systems of Innovation, Triple Helix and Mode-2. Further, the authors examine the main drivers, constraints and barriers to this engagement, and the typology of those with a vested interest in its development. Ultimately exploring how higher education institutions in SSA engage with, and transfer knowledge to, different external stakeholders, this book will be of value to academics involved with the study of higher education and science, innovation studies, the sociology of education, and education and development more broadly. In addition, politicians, administrators, and practitioners related to higher education, science, and innovation will also find the book of use"--
Introduction -- University and academics' societal engagement: main concepts -- Same but different? SSA as knowledge society and economy -- Knowledge producers in SSA: higher education institutions -- Features of knowledge produced in Sub-Saharan Africa -- Characteristics and typologies of stakeholders and knowledge users in SSA -- Forms and channels of knowledges transfer between university and external stakeholders in Sub-Sahara Africa -- Outputs, outcomes and benefits of university and academics' societal engagement and knowledges transfer in Sub-Sahara Africa -- Main drivers and constraints or barriers to university's societal engagement and knowledge transfer -- (Un-)fitness of conventional approaches to university and academics' societal engagement in Sub-Saharan Africa and presentation of an alternative analytical framework -- Afterword.
Keywords: Educational sociology -- Africa, Sub-Saharan.; Education, Higher -- Africa, Sub-Saharan.; Knowledge, Sociology of; EDUCATION / General; EDUCATION / Comparative